Models and Strategies for Management of Higher Education Public Relations - Yelvi Apriandini; Fazza Erwina Dwi; Bradley Setiyadi (Edumaspul: Jurnal Pendidikan, 2024)
The aim of this research is to find out models and strategies for managing higher education public relations. The research method is library research. Library research aims to collect data or information in the library and then use it as a basis for research. The research results show that strategy can be interpreted as a comprehensive plan to achieve targets even though there is no guarantee of success. Strategy is often associated with the terms tactics, techniques and methods, these three terms actually only remain within the strategy environment, only having more practical, narrow and detailed implications. Public relations models that can be used globally by all audiences according to the needs of the four models include: prees agentry with the type of one-way communication with propaganda. Public information with the type of one-way communication and disseminating correct and accurate information. Two-way asymmetrical type of two-way communication with scientific persuasion techniques. Two way symmetrical with two-way communication type to build mutual understanding.